Description and life-history traits of a new species of Proceraea with larvae infecting Abietinaria turgida (Polychaeta, Syllidae & hydrozoa, sertulariidae) - Britayev, T. A.; San Martin, G. L. A. (Ophelia, 2001)
A new species of the genus Proceraea (Polychaeta, Syllidae, Autolytinae), P. rzhavskyi, is described. Many specimens of this species at different stages of development were found within the hydrothecae and mucous tubes attached to colonies of the sertulariian hydrozoan Abietinaria turgida (Clark, 1867) at the coast of Mednyy Island, the Commander Islands, Northwest Pacific, 5-12 m depth, in August 1986. Larvae and juveniles are present within the hydrothecae from very early stages of development, which appears to be direct. This is the first report of a polychaete with symbiotic larval stages and free-living adults. The smallest specimens have a yolk, a single pair of eyes, and a tuft of short cilia at the apical part of prostomium, but lack setae. As larvae grow, the yolk and the tuft of cilia disappear. Setae and dorsal cirri appear on several anterior segments, the pharynx develops, and juveniles start feeding upon the host. Finally, they occupy the entire cavity of the hydrothecae. A conspicuous tubular addition to the hydrotheca is formed distally as a result of infestation. Upon reaching 10-11 setigers, the juveniles leave the hydrotheca, build mucous tubes attached to the stem or branches of the colony and continue their growth up to the adult stage. The proventriculus and the teeth of the trepan are formed when the worms leave the hydrothecae. Unlike Autolytus all the stages lack ciliary bands on the body. A female stolon (sacconereis) was examined. Proceraea rzhavskyi differs from closely related species, P. okadai and P. mukaishiraus, in structure of the trepan and length of head appendages and nuchal epaulettes. Descriptor: Abietinaria turgida
Kristian Fauchald's Polychaeta DB Kristian Fauchald's Polychaeta DB